A systematic review of ketamine for the treatment of depression among older adults. (30th June 2020) - Gupta, Aarti; Dhar, Romika; Patadia, Palak; Funaro, Melissa; Bhattacharya, Gargi; Farheen, Syeda A.; Tampi, Rajesh R.
Abstract: Objective: To review the currently available data on the use of ketamine in the treatment of depression among older adults from randomized controlled studies. Design: Randomized controlled trials. Setting: Variable. Participants: 60 years and older with depression. Intervention: Ketamine. Measurements: Change in Montgomery–Asberg Depression Rating Scale (MADRS) scores. Results: Two studies met the inclusion criteria. The first study showed a significant reduction in depression symptoms with use of repeated subcutaneous ketamine administration among older adults with depression. The second study failed to achieve significance on its primary outcome measure but did show a decrease in MADRS scores with intranasal ketamine along with a higher response and remission rates in esketamine group compared with the placebo group. The adverse effects from ketamine generally lasted only a few hours and abated spontaneously. No cognitive adverse effects were noted in either trial from the use of ketamine. Conclusions: The current evidence for use of ketamine among older adults with depression indicates some benefits with one positive and one negative trial. Although one of the trials did not achieve significance on the primary outcome measure, it still showed benefit of ketamine in reducing depressive symptoms. Ketamine was well tolerated in both studies with adverse effects being mild and transient.